Evaluation of Three Glycoprotein G2-Based Enzyme Immunoassays for Detection of Antibodies to Herpes Simplex Virus Type 2 in Human Sera - Eis-Hübinger, Anna Maria (American Society for Microbiology, 1999)
Three new glycoprotein G-based enzyme immunoassays (ETI-HSVK-G 2, Sorin Diagnostics Biomedica [assay A]; HSV Type 2 Specific IgG ELISA, Gull Laboratories, Inc. [assay B]; Cobas Core HSV-2 IgG EIA, Roche [assay C]) for the detection of herpes simplex virus (HSV) type 2 (HSV-2)-specific antibodies were evaluated. By testing sera from 25 individuals with culture-proven HSV-2 infection, the assays showed a sensitivity of 96%. The specificities, evaluated with sera from 70 HSV antibody-negative children, 75 HSV antibody-positive children, and 69 HSV antibody-negative adults, were 100% for assay A, 96.2% for assay B, and 97.8% for assay C, respectively. Discrepant results by any of the three assays, i.e., reactivity of a specimen in only one or two assays, occurred with similar frequencies for HSV-seronegative individuals as well as HSV-seropositive children and adults. For sera with discrepant results, the positive reactivity was mostly low. Thus, for determination of the prevalence of HSV-2 antibodies, only concordantly positive results were considered. On the basis of the results obtained with sera from 41 adults with culture-proven HSV-1 infection and from 173 HSV-antibody-positive pregnant women, the HSV-2 seroprevalence was 9.8%. The results show that the new glycoprotein G2-based enzyme immunoassays are useful tools for the detection of type-specific HSV-2 antibodies. However, if only one assay is performed, careful interpretation of the results is indicated, especially if the exhibited reactivity is low, and for determination of the definitive HSV-2 serostatus, confirmatory assays may still be necessary.